What is the Short-term and Long-term Relationship between Renewable Energy and Investment in Economic Growth? - Heru wahyudi; Widia Anggi Palupi (International Journal of Energy Economics and Policy, 2023)
The topics of energy, environment, natural resources, and economics have recently remained a topic of conversation. Thus, this study aims to determine the short-term and long-term influence between sustainable energy, CO2, oil rents, and investment on economic growth in ASEAN countries. Based on the purpose of the study, this study used the Vector Error Correction Model (VECM) method with the help of Eviews 10. All variables used in this study were cointegrated in the long term. So that renewable energy consumption helps economic growth in ASEAN countries; in other words, renewable energy consumption positively affects economic growth over time. Meanwhile, environmental damage proxied by CO2 hinders economic growth in the long run. This study also shows that ASEAN countries do not experience the curse of natural resources. This can be seen from the value of oil rents has a significant positive effect on economic growth. Meanwhile, investment in ASEAN has not improved the economy, so collaboration from all parties is needed to realize the welfare of the people projected with increased economic growth.